Formulation and nutritional facts in respect of bakery products of Peshawar and Mardan divisions - Khattak, Iftikhar Alam; Khan, Alam; Khattak, Muhammad Muzaffar Ali Khan; Khattak, Mohammad Saeed (Agricultural University, Peshawar, 2003)
Data for ingredients formulation and ingredients composition of eight type of pastries, tour type of cakes, two type of crackers and miscellaneous items like bread (double roti), kheer, bun, cream roll and patties available at the 106 randomly selected baker's shops of Mardan and Peshawar divisions, was collected Chemical composition and caloric values of samples of these products collected from 10% of the selected shops were determined. The average ingredient composition of pastries was 19% sugar, 31% fat and 26% cake. The average ingredient composition of cakes was 43% flour, 19% sugar, 3% milk and 18% fat. The average ingredient composition of cracker was 66% sugar and 14% butter. In cracker cheese, 33% cheese was an additional ingredient. The ingredient composition of the miscellaneous items were 16-52% flour, 7-22 % sugar, 4-28% milk and 4-29% fat. In bread (double roti), 22% egg and in patties 22% meat were the additional ingredients. The protein contents of these products ranged from 3.0% (bread) to 21.0% (patties). The carbohydrate contents ranged from 12.45% (patties) to 56.01% (cream roll). The fat contents ranged from 8.02% (kheer) to 48.361,0 (patties). The other nutrients determined were moisture, (4.17-43.21%.), ash (0.70-1.92%) and fiber (1.55-3.08%). The average energy contents of pastries, cakes, crackers, double roti, kheer, bun, cream roll and patties were 453. 483. 496. 425. 248, 398. 508 and 557 Kcal/100g of the products respectively The data demonstrated that bakery products were low in protein and high in fat. In the light of this research, bakery products should be consumed with care to avoid the over weight and obesity problems.